Interfund Lending in Mutual Fund Families: Role in Liquidity Management - Agarwal, Vikas; Zhao, Haibei (Review of Financial Studies, 2019)
The Investment Company Act of 1940 restricts interfund lending and borrowing within a mutual fund family, but families can apply for regulatory exemptions to participate in such transactions. We find that the monitoring mechanisms and investment restrictions influence the family’s decision to apply for the interfund lending programs. We document several benefits of such programs for equity funds. First, participating funds reduce cash holdings and increase investments in illiquid assets. Second, fund investors exhibit less run-like behavior. Third, it helps mitigate asset fire sales after extreme investor redemptions. Offsetting these benefits, money market funds in participating families experience investor outflows. Received May 26, 2018; editorial decision November 27, 2018 by Editor Itay Goldstein. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.